Edible Mushrooms as a Potential Component of Dietary Interventions for Major Depressive Disorder - Agata Fijałkowska; Karol Jędrejko; Katarzyna Sułkowska-Ziaja; Marek Ziaja; Katarzyna Kała; Bożena Muszyńska (Foods, 2022)
Dietary interventions for people suffering from major depressive disorder (MDD) are an ongoing field of research. In this article, we present a comprehensive background for understanding the possibility of using edible medicinal mushrooms as an adjunctive treatment for MDD. We start with a brief history of MDD, its diagnosis, epidemiology and treatment, and the effects of diet on depression symptoms, followed by a review of neurobiological, behavioral, and clinical studies of medicinal mushrooms. We specifically highlight the results of preclinical and clinical studies on dietary supplementation with three selected mushroom species: Lion’s mane (Hericium erinaceus), Caterpillar mushroom (Cordyceps militaris), and Lingzhi/Reishi (Ganoderma lucidum). Preliminary small-sample clinical studies suggest that Lion’s mane can influence well-being of humans. In the case of Reishi, the results of clinical studies are equivocal, while in the case of Caterpillar Mushroom, such studies are underway. Edible mushrooms contain 5-hydroxy-L-tryptophan (5-HTP), which is a direct precursor of serotonin—a neurotransmitter targeted in pharmacotherapy of MDD. Therefore, in light of the well-recognized role of stress as a pathogenic factor of MDD, we also describe the neurobiological mechanisms of the interaction between stress and serotonergic neurotransmission; and summarize the current state of knowledge on dietary supplementation with 5-HTP in MDD.